Grammatical Interpretation in Elong Ugi Mappadendang - Nur Fadilah; Usman Usman; Suarni Syam Saguni; Andi Agussalim Aj (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study aims to describe the grammatical interpretation in elong Ugi Mappadendang by using Frederich Schleirmacher's Hermeneutics theory. The type of research used is descriptive qualitative. The source of the research is elong Ugi Mappadendang which was created by Abdullah Alamudi and Andi Siti Nurhani Sapada, while the object of the research is the words and phrases in the text that are included in Frederich Schleirmacher's Hermeneutics theory. The results of the study indicate that there is a grammatical interpretation through the existence of parables, repetition, emphasis and word linkages that describe the Bugis people who are diligent and work hard to fulfill their needs in order to survive, regarding previous beliefs in the existence of Gods who give blessings and salvation, and the imposition is mandatory and brings goodness and the participation of the Bugis community in carrying out the Mappadendang tradition so that the preservation of the Mappadendang tradition grows in the Bugis community.Keywords: Grammatical Interpretation, Hermeneutics, Mappadendang